2005
DOI: 10.1111/j.0022-1112.2005.00661.x
|View full text |Cite
|
Sign up to set email alerts
|

Is white muscle anaerobic glycolysis capacity indicative of competitive ability in Arctic charr?

Abstract: Food ingestion to assess dominance status, indicated that dominant Arctic charr Salvelinus alpinus displayed significantly higher white muscle pyruvate kinase (PK) and lactate dehydrogenase (LDH) activities compared to subordinate fish [PK = 429·57 ± 76·37 v. 331·00 ± 61·73 U g−1 tissue (P = 0·022) and LDH = 929·33 ± 61·03 v. 775·25 ± 110·96 U g−1 tissue; (P = 0·0007)].

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 53 publications
1
17
0
Order By: Relevance
“…Regulation of glycogen phosphorylase (GP) by phosphorylation is indicated with P. GS p glycogen synthase; PEPCK p phosphoenolpyruvate carboxykinase; PK p pyruvate kinase; b 2 p b 2 -adrenoceptor; GR p glucocorticoid receptor; Glut2 p glucose transporter 2. increase both mRNA abundance and enzyme activity of PEPCK Vijayan et al 2003), responses that are thought to increase glucose production to meet the energetic demands of dealing with stress, and to restore liver glycogen reserves poststress . Subordinate trout also exhibited lower muscle (Le François et al 2005) and hepatic pyruvate kinase (PK) activities than dominant trout, as did fasted animals (DiBattista et al 2006). Reduced reliance on glycolysis is consistent with an animal that is metabolizing onboard energy reserves rather than making use of incoming nutrients ( fig.…”
Section: Introductionmentioning
confidence: 78%
See 1 more Smart Citation
“…Regulation of glycogen phosphorylase (GP) by phosphorylation is indicated with P. GS p glycogen synthase; PEPCK p phosphoenolpyruvate carboxykinase; PK p pyruvate kinase; b 2 p b 2 -adrenoceptor; GR p glucocorticoid receptor; Glut2 p glucose transporter 2. increase both mRNA abundance and enzyme activity of PEPCK Vijayan et al 2003), responses that are thought to increase glucose production to meet the energetic demands of dealing with stress, and to restore liver glycogen reserves poststress . Subordinate trout also exhibited lower muscle (Le François et al 2005) and hepatic pyruvate kinase (PK) activities than dominant trout, as did fasted animals (DiBattista et al 2006). Reduced reliance on glycolysis is consistent with an animal that is metabolizing onboard energy reserves rather than making use of incoming nutrients ( fig.…”
Section: Introductionmentioning
confidence: 78%
“…Social status also was found to modify muscle (Le François et al 2005) and liver glucose metabolism (DiBattista et al 2006), and these changes in metabolism may also contribute to differences in growth with social status. Hepatic phosphoenolpyruvate carboxykinase (PEPCK) activity in subordinate trout was significantly higher than that in dominant or control trout, suggesting an enhanced gluconeogenic potential (DiBattista et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Higher glycolytic capacities in rapidly growing fish have been reported in many studies (Pelletier et al 1994;Segner and Verreth 1995;Imsland et al 2006). It has been suggested that once food becomes available, the correlation between glycolytic enzymes and growth rate facilitates the maintenance of good swimming capacity and aggressive behaviour once food becomes available (Le François et al 2005). The persistence of a catabolic capacity and the uncoupling of glycolytic and aerobic metabolism enzymes during periods of food restriction may be an adaptative mechanism that ensures that the food-restricted fish can maintain a relatively high metabolism and rapidly resume growth upon refeeding.…”
Section: Figmentioning
confidence: 99%
“…Numerous studies have shown that, in certain circumstances, aggressive fish grow and survive better. For example, dominant Arctic char (Salvelinus alpinus) have better nutrient reserves and grow faster than do subordinate fish (Le François et al 2005). In general, aggressive fish tend to do well compared to their nonaggressive companions at high densities in simple environments with predictable food but poorly in complex environments with unpredictable food and low densities (for a review, see Damsgaard and Huntingford 2012).…”
Section: Direct Effects Of Level Of Aggressivenessmentioning
confidence: 99%